Supraspinal gene transfer by intrathecal adeno-associated virus serotype 5 - Schuster, Daniel J.; Belur, Lalitha R.; Riedl, Maureen S.; Schnell, Stephen A.; Podetz-Pedersen, Kelly M.; Kitto, Kelley F.; McIvor, R. Scott; Vulchanova, Lucy; Fairbanks, Carolyn A. (Frontiers in Neuroanatomy, 2014)
We report the pattern of transgene expression across brain regions after intrathecal delivery of adeno-associated virus serotype 5 (AAV5). Labeling in hindbrain appeared to be primarily neuronal, and was detected in sensory nuclei of medulla, pontine nuclei, and all layers of cerebellar cortex. Expression in midbrain was minimal, and generally limited to isolated neurons and astrocytes in the cerebral peduncles. GFP immunoreactivity (-ir) in thalamus was most prominent in medial geniculate nucleus, and otherwise limited to posterior nuclei of the dorsal and lateral margins. Labeling was also observed in neurons and astrocytes of the hippocampal formation and amygdaloid complex. In the hippocampal formation, GFP-ir was found in neuronal cell bodies of the rostral ventral portion, but was largely restricted to fiber-like staining in the molecular layer of dentate gyrus and stratum lacunosum-moleculare of the rostral dorsal region. GFP-ir was seen in neurons and astroglia throughout caudal cortex, whereas in rostral regions of neocortex it was limited to isolated astrocytes and neurons. Labeling was also present in olfactory bulb. These results demonstrate that intrathecal delivery of AAV5 vector leads to transgene expression in discrete CNS regions throughout the rostro-caudal extent of the neuraxis. A caudal-to-rostral gradient of decreasing GFP-ir was present in choroid plexus and Purkinje cells, suggesting that spread of virus through cerebrospinal fluid plays a role in the resulting transduction pattern. Other factors contributing to the observed expression pattern likely include variations in cell-surface receptors and inter-parenchymal space.